Use of chemically modified aquatic macrophytes to remove industrial dyes in aqueous media - Andrade, Luana Lins de; Passos, Desiree Alves; Asencios, Yvan Jesus Olortiga; Fernandes, Sidney (STUDIES IN ENVIRONMENTAL AND ANIMAL SCIENCES, 2025)
This work aimed to obtain biosorbents based on aquatic macrophytes present in the Baixada Santista, which can be used in the removal of industrial dyes present in aqueous systems. Evaluate the removal capacity of industrial dyes by different chemically modified macrophytes. Sets of specimens of Azolla caroliniana at Lagoa da Saudade, Nova Cintra, Santos - SP, samples of Lemna minor were collected in a stream at the entrance of the Jardim Piratininga neighborhood and samples of Egeria densa purchased at an aquarium store in São Vicente-SP. The aquatic macrophytes were analyzed in order to estimate the adsorption potential of the methylene blue dye and to understand the variables involved in the biosorption process of the chosen macrophyte. The concentration of elements and/or chemical substances in macrophytes will serve as indicators of pollutants and probably new contributions to science, since so far, no study on the subject has been carried out in the metropolitan region of Baixada Santista. Among the observations made, it was found that as we increase the amount of macrophytes, the absorbance decreases, increasing the percentage of adsorption efficiency, showing the capacity of macrophytes to adsorb methylene blue. In addition to serving as bioaccumulators of dyes, they also serve as a shelter for small animals, often found. It is believed that by the end of the project we will have rich information about the importance of aquatic macrophytes for the environment, helping the recovery of water bodies where anthropogenic action may have occurred.